2018
DOI: 10.1111/psyp.13311
|View full text |Cite
|
Sign up to set email alerts
|

An ERP study of cross‐modal rhyming: Influences of phonology and orthography

Abstract: In a cross‐modal rhyming study with visual pseudoword primes and auditory word targets, we found a typical ERP rhyming effect such that nonrhyming targets elicited a larger N400/N450 than rhyming targets. An orthographic effect was also apparent in the same 350‐ to 600‐ms epoch as the phonological effect: The rhyming effect for targets with rime orthography that did not match their primes' (e.g., tain‐“sane”) was smaller over the left hemisphere than the rhyming effect for targets with rime orthography that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…In language comprehension studies, the N400 effect has been typically reported when a semantic congruent condition is compared to a semantic incongruent condition in the time window of 200–600 ms after stimulus onset, and it is most pronounced in centro‐parietal electrode sites (Kutas & Federmeier, 2011). In reading, this component is thought to reflect semantic (Du et al., 2014) and phonological (Deacon et al., 2004; Mitra & Coch, 2019) processing, which occurs after orthographic processing (Chen & Peng, 2001; Chen et al., 2003; Perfetti & Tan, 1998). Although we mainly focused on orthographic processing in this study, we used the N400 component (a) as an auxiliary index to examine whether or not participants completed the reading task well, and (b) to examine whether or not motor information influences later‐stage processes in reading.…”
Section: Introductionmentioning
confidence: 99%
“…In language comprehension studies, the N400 effect has been typically reported when a semantic congruent condition is compared to a semantic incongruent condition in the time window of 200–600 ms after stimulus onset, and it is most pronounced in centro‐parietal electrode sites (Kutas & Federmeier, 2011). In reading, this component is thought to reflect semantic (Du et al., 2014) and phonological (Deacon et al., 2004; Mitra & Coch, 2019) processing, which occurs after orthographic processing (Chen & Peng, 2001; Chen et al., 2003; Perfetti & Tan, 1998). Although we mainly focused on orthographic processing in this study, we used the N400 component (a) as an auxiliary index to examine whether or not participants completed the reading task well, and (b) to examine whether or not motor information influences later‐stage processes in reading.…”
Section: Introductionmentioning
confidence: 99%
“…The N450 effect is strongly right-lateralized for orthographically dissimilar stimuli (e.g., MAKE-ACHE) and midline for similar stimuli (e.g., PLEA-FLEA) for reasons that are currently unclear (Michael D. Rugg & Barrett, 1987). This effect is also found for pronounceable pseudowords (Ackerman et al, 1994; M. D. Rugg, 1984a), single letters (Coch, Hart, & Mitra, 2008), auditory words (Mitra & Coch, 2019;Perez-Abalo, Rodriguez, Bobes, Gutierrez, & Valdes-Sosa, 1994), and even nameable pictures (Barrett & Rugg, 1990;Coch, 2018). Its generator site is unknown and localizing it will be a secondary goal for this study.…”
Section: Introductionmentioning
confidence: 85%
“…However, in a direct comparison, the typical N400 lexicality effect was present such that nonwords elicited more negative N400s than words (e.g., Bentin, 1987; Deacon et al., 2004; Holcomb et al., 2002; Nobre & McCarthy, 1994; Rugg & Nagy, 1987). Previous studies have shown that N400 amplitude can be sensitive to the degree of mismatch between orthography and phonology during word processing (e.g., Mitra & Coch, 2019; Weber‐Fox et al., 2003), but the task in these studies (rhyming) focused on phonology in a way that an LDT (as used here) does not, which may have biased processing (e.g., see Pattamadilok et al., 2011, for task‐specific effects). Given the N1 results with the same stimuli, 32 participants, and over 70 trials included in individual ERP averages for both rule‐breaking and rule‐following words and nonwords, on average, the lack of N400 rule effects in these analyses does not appear to be related to a lack of power.…”
Section: Discussionmentioning
confidence: 99%